Pathogenesis, multi-omics research, and clinical treatment of psoriasis. Issue 133 (December 2022) - Yu, Jiadong; Zhao, Qixiang; Wang, Xiaoyan; Zhou, Hong; Hu, Jing; Gu, Linna; Hu, Yawen; Zeng, Fanlian; Zhao, Fulei; Yue, Chengcheng; Zhou, Pei; Li, Guolin; et al.
Abstract: Psoriasis is a common inflammatory skin disease involving interactions between keratinocytes and immune cells that significantly affects the quality of life. It is characterized by hyperproliferation and abnormal differentiation of keratinocytes and excessive infiltration of immune cells in the dermis and epidermis. The immune mechanism underlying this disease has been elucidated in the past few years. Research shows that psoriasis is regulated by the complex interactions among immune cells, such as keratinocytes, dendritic cells, T lymphocytes, neutrophils, macrophages, natural killer cells, mast cells, and other immune cells. An increasing number of signaling pathways have been found to be involved in the pathogenesis of psoriasis, which has prompted the search for new treatment targets. In the past decades, studies on the pathogenesis of psoriasis have focused on the development of targeted and highly effective therapies. In this review, we have discussed the relationship between various types of immune cells and psoriasis and summarized the major signaling pathways involved in the pathogenesis of psoriasis, including the PI3K/AKT/mTOR, JAK-STAT, JNK, and WNT pathways. In addition, we have discussed the results of the latest omics research on psoriasis and the epigenetics of the disease, which provide insights regarding its pathogenesis and therapeutic prospects; we have also summarized its treatment strategies and observations of clinical trials. In this paper, the various aspects of psoriasis are described in detail, and the limitations of the current treatment methods are emphasized. It is necessary to improve and innovate treatment methods from the molecular level of pathogenesis, and further provide new ideas for the treatment and research of psoriasis. Highlights: The relationship between various immune cells and psoriasis is discussed. Major signaling pathways involved in the pathogenesis of psoriasis are summarized. Results of the latest omics research on psoriasis are discussed. Treatment strategies and clinical trial observations for psoriasis are summarized.